Rabson–Mendenhall syndrome with recurrent cerebral infarcts caused by a novel INSR mutation. (24th January 2013) - Mohanan, Saritha; Chandrashekar, Laxmisha; Semple, Robert K.; Thappa, Devinder M.; Parameswaran, Narayanan; Negi, Vir S.; Ramassamy, Sivaranjini
Abstract Rabson–Mendenhall syndrome (RMS) is an autosomal recessive disorder characterized by extreme insulin resistance and certain characteristic phenotypic features. The primary defect lies in the insulin receptor and involves biallelic mutations that lead to a loss of function through various postulated defects. We present a 9‐year‐old female patient with RMS complicated by multiple cerebral infarcts, in whom genetic analysis revealed a novel insulin receptor mutation.